The consequence of destination image on travel motivation: evidence from Bangladesh ecotourism - Rahman, Mohammad Moshiur; Haque, A. K. M. Ahasanul; Suib, Fatin Husna (E-Palli LLC, Delaware, USA, 2022)
The precipitous expansion of ecotourism destinations has intensified competition in the tourism business. Thus, the present study investigates the connection between destination image and travel motivation that marketers must comprehend and focus on establishing eco tourism in Bangladesh. Despite a growing number of works on destination image, there has been little investigation on the relationship between travel motivation. Therefore, this study aims to evaluate the effect of destination image and travel motivation on tourists’ selection of ecotourism destinations. In contrast to previous research, which primarily focused on identifying destination features, this study employed a structured questionnaire directed at tourists during their on-site experiences. Using SPSS-SEM, the suggested structural model was evaluated with a sample of 326 tourists from various Bangladesh ecotourism destina tions. The results confirmed that “cognitive” and “affective” destination images significantly influence travel motivation. It also indicates a better understanding of the relationship and significant managerial implications for destination marketing managers.